Hubungan Risk Profile Dengan Kinerja Keuangan Bank Panin Dubai Syariah 2016-2020 - Firdaus, Firdaus; Fakhruddin, Imam; Jamiah, Jamiah; Saphira, Fitri; Safhira, Sahyu; Saifullah, Saifullah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This research was conducted to examine the correlate of Risk Profile (Non Performing Financing (NPF) and Financing Deposite Ratio (FDR) to Return on Asset (ROA).This research uses quantitatif method. The population of this research is the financial report Panin Dubai Syariah bank period 2016 through 2020. Sensus sampling method were used as samples determining, whre all the population is sampled. Analysis method with correlation pearson. The result of the research is Non Performing Financing/NPF has negative correlated and significant with Return on Asset (ROA) and Financing Deposite Ratio (FDR) has negative correlated and significant with Return on Asset (ROA). The implication of this research is that the poor NPF and FDR of Panin Dubai Syariah Bank have an impact on the company's ability to generate profits. High NPF and FDR lead to a decrease in ROA. For this reason, Panin Dubai Syariah Bank needs to maintain NPF and FDR in accordance with the minimum standards set by Bank Indonesia